2015
DOI: 10.1371/journal.pone.0123765
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Comparison of the Opinions of Physicians Working in Emergency and Trauma Surgery Departments at Tabriz and Vienna Medical Universities Regarding Family Presence during Resuscitation

Abstract: The present study evaluated the opinions of physicians working in the emergency and trauma surgery departments of Vienna Medical University, in Austria, and Tabriz Medical University, in Iran, regarding the presence of patients’ relatives during resuscitation. In a descriptive-analytical study, the data obtained from questionnaires that had been distributed randomly to 40 specialists and residents at each of the participating universities were analyzed. The questionnaire consisted of two sections aimed at capt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…These findings show that the attitude of the majority of Brazilian nurses and physicians towards FPDR was negative; they identified significant barriers and limitations to its implementation in practice – Similar results were found in a study carried out in Austria and Iran with 80 physicians working in ED (Soleimanpour et al. ). Our research shows that the lack of physical space for families, the perception of being observed, and increased staff stress have been reported and remain constant concerns to the participants.…”
Section: Discussionsupporting
confidence: 82%
“…These findings show that the attitude of the majority of Brazilian nurses and physicians towards FPDR was negative; they identified significant barriers and limitations to its implementation in practice – Similar results were found in a study carried out in Austria and Iran with 80 physicians working in ED (Soleimanpour et al. ). Our research shows that the lack of physical space for families, the perception of being observed, and increased staff stress have been reported and remain constant concerns to the participants.…”
Section: Discussionsupporting
confidence: 82%
“…, Soleimanpour et al . ). This paper provides the first in‐depth examination of decision‐making around family presence during resuscitation (FPDR) and offers an enhanced understanding of rationales for practice.…”
Section: Introductionmentioning
confidence: 97%
“…Like Tercier (2008), we believe a 'good' sudden death involves family in the last minutes of life. Yet, many family members are separated from their potentially dying loved ones during resuscitation events (Taraghi et al 2014, Soleimanpour et al 2015. This paper provides the first in-depth examination of decision-making around family presence during resuscitation (FPDR) and offers an enhanced understanding of rationales for practice.…”
Section: Introductionmentioning
confidence: 99%
“…Current literature has many examples of clinicians separating family who wish to be present from their loved ones during unsuccessful resuscitation events, thus denying them the chance to say goodbye (Gunes & Zaybak, ; Soleimanpour et al., ; Taraghi et al., ). Decisions that impact the welfare of patients and families usually involve an ethical lens, where the benefits and harms of such decisions are weighed by clinicians and the action with the best‐predicted outcome is chosen (Kerridge, Lowe, & Stewart, ).…”
Section: Introductionmentioning
confidence: 99%
“…Family presence during resuscitation has created contentious debate for decades. Despite known benefits, and support from many professional bodies and the public, some clinicians do not support the practice and commonly separate family who wish to be present from their loved ones during resuscitation (Gunes & Zaybak, ; Soleimanpour et al., ; Taraghi et al., ). Consistently low resuscitation survival rates of 6%–13% (Berdowski, Berg, Tijssen, & Koster, ; Sasson, Rogers, Dahl, & Kellermann, ) mean that if FPDR is denied, family are not able to be with their loved ones at the end of life.…”
Section: Introductionmentioning
confidence: 99%